Whole‐body mapping of spatial acuity for pain and touch. Issue 6 (6th June 2014) - Mancini, Flavia; Bauleo, Armando; Cole, Jonathan; Lui, Fausta; Porro, Carlo A.; Haggard, Patrick; Iannetti, Gian Domenico
<x xml:space="preserve">Abstract</x> Objective Tactile spatial acuity is routinely tested in neurology to assess the state of the dorsal column system. In contrast, spatial acuity for pain is not assessed, having never been systematically characterized. More than a century after the initial description of tactile acuity across the body, we provide the first systematic whole‐body mapping of spatial acuity for pain. Methods We evaluated the 2‐point discrimination thresholds for both nociceptive‐selective and tactile stimuli across several skin regions. Thresholds were estimated using pairs of simultaneous stimuli, and also using successive stimuli. Results and interpretation These two approaches produced convergent results. The fingertip was the area of highest spatial acuity, for both pain and touch. On the glabrous skin of the hand, the gradient of spatial acuity for pain followed that observed for touch. On the hairy skin of the upper limb, spatial acuity for pain and touch followed opposite proximal–distal gradients, consistent with the known innervation density of this body territory. Finally, by testing spatial acuity for pain in a rare participant completely lacking Aβ fibers, we demonstrate that spatial acuity for pain does not rely on a functioning system of tactile primary afferents. This study represents the first systematic characterization of spatial acuity for pain across multiple regions of the body surface. Ann Neurol 2014;75:917–924